Extracellular Secretion of Noncatalytic Plant Cell Wall-Binding Proteins by the Cellulolytic Thermophile Caldicellulosiruptor bescii - Yokoyama, Hiroshi (J Bacteriol, 2014)
Caldicellulosiruptor bescii efficiently degrades cellulose, xylan, and native grasses at high temperatures above 70°C under anaerobic conditions. C. bescii extracellularly secretes multidomain glycoside hydrolases along with proteins of unknown function. In this study, we analyzed the C. bescii proteins that bind to the cell walls of timothy grass by using mass spectrometry, and we identified four noncatalytic plant cell wall-binding proteins (PWBPs) with high pI values (9.2 to 9.6). A search of a conserved domain database showed that these proteins possess a common domain related to solute-binding proteins. In addition, 12 genes encoding PWBP-like proteins were detected in the C. bescii genomic sequence. To analyze the binding properties of PWBPs, recombinant PWBP57 and PWBP65, expressed in Escherichia coli, were prepared. The PWBPs displayed a wide range of binding specificities: they bound to cellulose, lichenan, xylan, arabinoxylan, glucuronoxylan, mannan, glucomannan, pectin, oligosaccharides, and the cell walls of timothy grass. The proteins showed the highest binding affinity for the plant cell wall, with association constant (K(a)) values of 5.2 × 10(6) to 44 × 10(6) M(−1) among the insoluble polysaccharides tested, as measured using depletion binding isotherms. Affinity gel electrophoresis demonstrated that the proteins bound to the acidic polymer pectin most strongly among the soluble polysaccharides tested. Fluorescence microscopic analysis showed that the proteins bound preferentially to the cell wall in a section of grass leaf. Binding of noncatalytic PWBPs with high pI values might be necessary for efficient utilization of polysaccharides by C. bescii at high temperatures.